3D printing of graphene-based polymeric nanocomposites for biomedical applications - Silva, Magda (2021)
Additive manufacturing techniques established a new paradigm in the manufacture of composite materials providing a simple solution to build complex, custom designed shapes. In the biomedical field, 3D printing enabled the production of scaffolds with patient-specific requirements, controlling product architecture and microstructure, and have been proposed to regenerate a variety of tissues such as bone, cartilage, or the nervous system. Polymers reinforced with graphene or graphene derivatives have demonstrated potential interest for applications that require electrical and mechanical properties as well as enhanced cell response, presenting increasing interest for applications in the biomedical field. The present review focuses on graphene-based polymer nanocomposites developed for additive manufacturing fabrication, provides an overview of the manufacturing techniques available to reach the different biomedical applications, and summarizes relevant results obtained with 3D printed graphene/polymer scaffolds and biosensors.